Interpreting Samson Agonistes - Wittreich, Joseph Anthony (Princeton legacy library, 1986)
Joseph Wittreich reveals Samson to be an intensely political work that reflects the heroic ambitions and failings of the Puritan Revolution and the tragic ambiguities of the era. He sees in the work not the purveyance of Medieval and early Renaissance typological associations but an interrogation of them and a consequent movement away from them. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.